2011
DOI: 10.1111/j.1440-172x.2011.01970.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐efficacy associated with self‐management behaviours and health status of South Koreans with chronic diseases

Abstract: Although prior research in Western societies has revealed an association between self-efficacy and both self-management behaviours and better health status, little is known about the applicability of this association in Korean populations. We examined the differences in self-management behaviours and health status among three groups according to the level of self-efficacy (high, moderate and low). We used a descriptive and correlational design, and administrated a questionnaire to 322 Korean patients with diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
2
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 24 publications
8
27
2
3
Order By: Relevance
“…As a fundamental part of chronic care, self-management is defined as an individual's ability to manage symptoms, treatments, lifestyle changes, control physical, mental and psychological problems, and have a desirable life along with a chronic problem. Patients with improved self-management abilities can properly monitor problems related to their disease every day, try to find solutions and discuss them with healthcare providers (9,11).…”
Section: Introductionmentioning
confidence: 99%
“…As a fundamental part of chronic care, self-management is defined as an individual's ability to manage symptoms, treatments, lifestyle changes, control physical, mental and psychological problems, and have a desirable life along with a chronic problem. Patients with improved self-management abilities can properly monitor problems related to their disease every day, try to find solutions and discuss them with healthcare providers (9,11).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, self-efficacy contributes to the patient's confidence in their own ability to function in a healthy manner, and to perceive the changes taking place in conjunction with daily difficulties (Lorig, Stewart Ritter, Gonzalez, Laurent, & Lynch, 1996;Yoo, Kim, Jang, & You, 2011). Self-efficacy promotes improvements or at least stabilazes the patients' current state of health (Weng, Dai Huang, Chiang, 2010, as referred to Yoo, Kim, Jang, & You, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy is one's belief in one's ability to organize and execute specific actions or react in specific ways in order to achieve one's goals (Bandura, 1977;Kaul, 2010). Self-efficacy reflects the person's belief that he or she is able to organize and integrate the management of emotions, physical and social behaviors in order to be able to find solutions to everyday problems (Lorig, Stewart Ritter, Gonzalez, Laurent, & Lynch, 1996;Yoo, Kim , Jang & You, 2011). Also, studies have shown that high levels of self-efficacy contribute to the improvement of one's health, positive selfevaluation and management of appropriate behaviors (Weng, Dai Huang, Chiang, 2010;Yoo, Kim, Jang, & You, 2011).…”
Section: Self-efficacymentioning
confidence: 99%
“…Social cognitive theory also provides a structure and processes to inform the development of an intervention that can improve the level of self-efficacy in an individual (Lenz & Shortridge-Baggett, 2002;van de Laar & van der Bijl, 2001). Hence, SCT is recognised as one of the most frequently used theories in studying health behaviour in people with chronic disease (Dang, Deoisres, Keeratiyutawong, & Baumann, 2013;Dao, 2012;Ha, Hu, Petrini, & McCoy, 2014;Wu et al, 2007;Yoo, Kim, Jang, & You, 2011), including those with CKD (Balaga, 2012;Byrne et al, 2011;Kazawa & Moriyama, 2013;Tsay, 2003;Weng, Dai, Huang, & Chiang, 2010;Wierdsma et al, 2011).…”
Section: 1mentioning
confidence: 99%